PENERAPAN GOOD UNIVERSITY GOVERNANCE TERHADAP KEPUASAN MAHASISWA DENGAN EXCELLENT SERVICE SEBAGAI VARIABEL MODERASI: (Studi Kasus Mahasiswa Institut Teknologi dan Bisnis Indonesia) - Tri Dessy Ratna Sari; Renny Maisyarah; Rahima Br Purba (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The objective of this research is to examine the impact of the implementation of effective university governance on student satisfaction and excellent service, with a focus on how excellent service moderates the relationship between university governance and student satisfaction at the Indonesian Institute of Technology and Business. This study utilized primary data and targeted a population of 2,501 students from the Indonesian Institute of Technology and Business between 2020-2023. Purposive sampling was employed, resulting in a sample size of 100 students. The analysis involved simple linear regression analysis and MRA (Moderated Regression Analysis) using SPSS (Statistical Package for the Social Science) software. The findings of this study demonstrate that good university governance has a positive and significant impact on student satisfaction, while excellent service does not enhance the influence of good university governance on student satisfaction. These findings have implications for university administrators and policymakers, as they emphasize the significance of implementing and maintaining effective governance practices to improve student satisfaction. Further research could explore other factors that may moderate the relationship between university governance and student satisfaction, providing a more comprehensive understanding of this relationship.